Keyakinan dan Kepatuhan Pengobatan Antiretroviral pada Pasien HIV - Cahyani, Nur; Wahyudin, Elly; M., Jamaluddin; Rahman, Latifah; Marzuki, Asnah; Arifin, Bustanul (FORIKES, 2023)
Reports regarding patient belief and medication adherence and the relationship between the two are still rare, especially in developing countries. This study aimed to determine belief, adherence, and the relationship between belief and adherence of patients with Human Immunodeficiency Virus to antiretroviral therapy. This research was conducted with a cross-sectional design. Participants were recruited from two health care facilities, namely hospitals and health centers. Participants who were recruited were currently undergoing antiretroviral treatment, aged at least 18 years, and signed a consent form. Participants filled out sociodemographic data and two questionnaires, namely the Beliefs about Medicines Questionnaire to assess belief in treatment and the Medication Adherence Rating Scale 5 to assess adherence to treatment. Statistical analysis was performed by Chi-square test. The results of this research show that the p-value = 0.000. It was concluded that belief in treatment was related to the level of adherence of participants in using antiretroviral therapy.Keywords: HIV patient; antiretroviral therapy; half; belief ABSTRAK Laporan terkait keyakinan dan kepatuhan pengobatan pasien serta hubungan di antara keduanya masih jarang dilaporkan, khususnya di negara sedang berkembang. Penelitian ini bertujuan untuk mengetahui keyakinan, kepatuhan, dan hubungan antara keyakinan dengan kepatuhan pasien dengan Human Immunodeficiency Virus terhadap terapi antiretroviral. Penelitian ini dilakukan dengan rancangan cross-sectional. Partisipan direkrut dari dua fasilitas pelayanan kesehatan, yaitu Rumah Sakit dan Puskesmas. Partisipan yang direkrut adalah yang sedang menjalani pengobatan antiretroviral, berusia minimal 18 tahun, dan menandatangani lembar persetujuan. Partisipan mengisi data sosiodemografi, dan dua kuesioner yaitu Beliefs about Medicines Questionnaire untuk menilai keyakinan terhadap pengobatan dan Medication Adherence Rating Scale 5 untuk menilai kepatuhan akan pengobatan. Analisis statistik dilakukan dengan uji Chi-square. Hasil penelitian menunjukkan nilai p = 0,000. Disimpulkan bahwa keyakinan akan pengobatan berhubungan terhadap tingkat kepatuhan partisipan dalam menggunakan terapi antiretroviral.Kata kunci: pasien HIV; terapi antiretroviral; keparuhan; keyakinan